Embedded Linux development using Yocto projects : learn to leverage the power of Yocto Project to build efficient Linux-based products /: learn to leverage the power of Yocto Project to build efficient Linux-based products. (2017) - Salvador, Otavio; Angolini, Daiane
No abstract available